Kierkegaard's Epistemology: A Response to Professor Steven M. Emmanuel's Paper "Kierkegaard on Knowledge and Faith" - Pojman, Louis P. (KIERKEGAARDIANA, 1991)
Kierkegaard's Epistemology: A Response to Professor Steven M. Emmanuel's Paper "Kierkegaard on Knowledge and Faith"